Over-Indebtedness and Problem Gambling in a General Population Sample of Online Gamblers - Håkansson, Anders; Widinghoff, Carolina (Frontiers in Psychiatry, 2020)
Background Online gambling has increased in recent years, including online casino games and live sports betting which constitute rapid gambling activities with significant potential for gambling-related harm. There is a paucity of research examining whether specific gambling patterns are related to problem gambling and over-indebtedness, when controlling for psychological distress, gender, and other risk factors. Methods A general population-based web panel of 1,004 online gamblers were examined in an online survey addressing problem gambling symptoms (the PGSI), psychological distress (Kessler- 6), past-30-day gambling activities, past-30-day gambling losses, history of subjective over-indebtedness and expected over-indebtedness in the near future, as well as socio-demographic data. Results In logistic regression analyses, problem gambling was associated with psychological distress, recent online casino gambling, and recent combined online casino gambling and live sports betting. History of over-indebtedness was associated with recent combined online casino gambling and live sports betting, and expected over-indebtedness was associated with online casino gambling. Problem gambling, and a history of having borrowed money for gambling, were markedly higher in online casino gamblers, compared to subjects not reporting this gambling activity. Problem gambling was markedly more common in women, but was not associated with gender in the adjusted analysis. Conclusions In online gamblers, high rates of problem gambling and over-indebtedness were seen, and online casino gambling (alone or in combination with live sports betting), was associated with remarkably increased risk. Gender distribution of problem gamblers was clearly in contrast to that found in previous problem gambling literature. These findings suggest regulations in the market of online casino gambling, and prevention of over-indebtedness in gambling-related borrowing, in consumer credit counselling and in mental health care. In particular, female gender may need to be addressed as a stronger risk factor than previously described.